Technical and Interpretative Aspects of Violin Performance in Chopin’s Nocturne No. 20 in C-Sharp - Lase, Jefri Aprillian; Simanjuntak, Hendrik L; Galingging, Kamaluddin (Pascasarjana Institut Seni Indonesia Padang Panjang, 2025)
This study examines the playing techniques and musical presentation of Nocturne No. 20 in C-Sharp Minor by Frederic Chopin when performed on the violin. Although originally composed for piano, this work has frequently been adapted for violin performance, presenting specific technical and interpretative challenges for performers. The purpose of this research is to analyze the violin playing techniques and expressive elements required to perform the piece effectively. This study employs a qualitative descriptive approach through musical analysis and literature review, supported by observations of the rehearsal and performance process. The analysis focuses on several important techniques applied in the performance, including legato, triplet, and trill techniques, as well as the use of musical dynamics such as piano, mezzo forte, diminuendo, and tempo indications like meno mosso. The findings show that the primary technical challenge in performing this work lies in maintaining smooth legato phrasing while preserving expressive musical interpretation. In addition, the performer must control bow pressure, finger placement, and rhythmic accuracy to achieve the expressive character typical of Chopin’s romantic musical style. The study demonstrates that the integration of technical mastery and musical interpretation plays a crucial role in delivering a convincing violin performance of Nocturne No. 20 in C-Sharp Minor. These findings contribute to the understanding of violin performance practices in adapting Romantic piano repertoire to violin interpretation